Rancang Bangun Alat Fiksasi Pemeriksaan Radiografi Ossa Pedis Proyeksi Ap dan Oblique - Pande Rahayu Sindu Yoga; Dea Reyangga (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
During the field work practice, the author observed that there were obstacles in placing pedis examinations on non-cooperative patients so that the examination was not optimal. This obstacle resulted in radiologists not being able to carry out their expertise properly. In addition, if the referring doctor asks for a repeat photo, it will give the patient an excessive radiation dose. With such patient conditions, a fixation device is needed so that the examination produced optimal results. Innovation efforts are needed to overcome this in order to improve services and prioritize patient safety. In addition, according to Lampignano & Kendrick, (2018), it is not permissible to force injured limbs or body parts into a certain position, the position must be adjusted according to needs. So that patients with multiple fractures require special treatment that is different from patients in general. The researcher designed a fixation device that can be used in the patient’s supine and sitting positions without having to lift the patient’s thigh, genu, and cruris bones and also without looking at the size of the patient’s feet.